Heterogeneity in corporate debt structures and the transmission of monetary policy - Fédéric Holm-Hadulla; Claire Thürwächter (European Central Bank (ECB), 2020)
We study how differences in the aggregate structure of corporate debt financing affect the transmission of monetary policy. Using high-frequency financial market data to identify monetary policy shocks in a panel of euro area countries, we find that: bond finance dampens the overall response of firm credit to monetary policy shocks in economies with a high initial share of bond- relative to bank-based finance; this effect weakens, and may even reverse, in economies with a low share of bond financing; and the dampening effect of a larger bond financing share also attenuates the ultimate impact of monetary policy on economic activity. These findings point to corporate bond markets acting as a "spare tire" in situations when bank lending contracts.
Keywords: E44; E52; G21; G23; 330; Firm Financing Structure; Bank Lending; Corporate Bonds; High-Frequency Identification; Local Projections